Electroweak and Strong Interactions Phenomenology, Concepts, Models - Scheck, Florian (Graduate Texts in Physics,, 2012)
Electroweak and Strong Interaction: Phenomenology, Concepts, Models, begins with relativistic quantum mechanics and some quantum field theory which lay the foundation for the rest of the text. The phenomenology and the physics of the fundamental interactions are emphasized through a detailed discussion of the empirical fundamentals of unified theories of strong, electromagnetic, and weak interactions. The principles of local gauge theories are described both in a heuristic and a geometric framework. The minimal standard model of the fundamental interactions is developed in detail and characteristic applications are worked out. Possible signals of physics beyond that model, notably in the physics of neutrinos are also discussed. Among the applications scattering on nucleons and on nuclei provide salient examples. Numerous exercises with solutions make the text suitable for advanced courses or individual study. This completely updated revised new edition contains an enlarged chapter on quantum chromodynamics and a widely updated chapter on neutrino physics.